Safety and efficacy of the use of large bore intermediate suction catheters alone or in combination for the treatment of acute cerebral venous sinus thrombosis: A multicenter experience. Issue 1 (February 2020) - Dandapat, Sudeepta; Samaniego, Edgar A; Szeder, Viktor; Siddiqui, Fazeel M; Duckwiler, Gary R; Kiddy, Ume; Guerrero, Waldo R; Zheng, Binbin; Hasan, David; Derdeyn, Colin; Ortega-Gutierrez, Santiago
Background and purpose: Systemic anticoagulation is the standard treatment for cerebral venous sinus thrombosis (CVST). Several endovascular techniques have been described as salvage therapy for anticoagulation refractory CVST cases. We aim to evaluate the safety and feasibility of endovascular aspiration thrombectomy using the new generation, large bore suction catheters alone or in combination with stentriever devices for the treatment of CVST. Methods: We collected data on 16 consecutive patients with CVST who received endovascular aspiration thrombectomy at three large academic centers. Second generation reperfusion catheters were used as a large bore suction catheter and advanced to the affected sinus using a coaxial technique. Suction was performed using pump suction. At times, a stentriever was used as an anchor to facilitate advancing the suction catheter and to increase thrombectomy capabilities. Results: Median decade of age was the 50s and nine patients were women. Fifty percent of the patients had multiple sinuses involved. All patients received systemic anticoagulation prior to endovascular aspiration thrombectomy. The most common reason to pursue endovascular aspiration thrombectomy in CVST patients was deterioration of initial clinical status (10/16). The mean time from admission to endovascular aspiration thrombectomy was 1.5 days (range 0–6 days). Good recanalization was obtained in all patients. There were no major peri-procedural complications. Most patients were discharged to either home or a rehabilitation facility. Conclusion: Endovascular aspiration treatment using large bore suction catheters for CVST is a safe and feasible approach for the treatment of anticoagulation refractory CVST. Heterogeneity of the clinical and radiological presentation requires further investigation to optimize patient selection before evaluating the efficacy of this technique in larger prospective studies.